Penguasaan balaghah dalam kalangan pelajar IPT / Raja Hazirah Raja Sulaiman - Raja Hazirah, Raja Sulaiman (2012)
This study is related to the mastery of Balaghah or Arabic Rhetoric among IPT students. The study aimed to know the level of university students on the Balaghah, and measure learning effectiveness in teaching at university level, as well as perceptions and knowledge of students to study, indirectly identifying the problems faced by students learning Arabic balaghah knowledge. A total of 200 students from the University of Sultan Zainal Abidin (UniSZA), Terengganu, have been implicated as a sample. These students are from the Contemporary Islamic Studies Faculty, representing five different departments. This study uses a questionnaire to obtain research data and process the data obtained using the Likert scale. Result of this study shows that the students have deep perceptions and interests on the Balaghah knowledge and the result also shown that the teaching of Balaghah in the chosen university at a moderate level, and static which should be increase for students at university level. This gives us the conclusion that measurement and methodology of teaching at the university level should be adjusted and changed by stages and in accordance with the level of students. Therefore some of the proposals put forward by researchers to the Ministry of Education (MOE), the management of universities and lecturers.